17‐alpha‐hydroxyprogesterone caproate versus vaginal progesterone suppository for the prevention of preterm birth in women with a sonographically short cervix: A randomized controlled trial. Issue 1 (24th October 2016) - Pirjani, Reihaneh; Heidari, Reza; Rahimi‐Foroushani, Abbas; Bayesh, Seyedehsara; Esmailzadeh, Arezoo
Abstract: Aim: The aim of this study was to compare 17‐alpha‐hydroxyprogesterone caproate (17OHP‐C) with vaginal progesterone suppository for the prevention of preterm birth in women with a sonographically short cervix and to evaluate the changes of the cervical length (CL) over time. Methods: In this prospective randomized controlled trial, eligible patients were asymptomatic pregnant women with a sonographically short cervix. The participants in group 1 ( n = 147) received vaginal progesterone suppositories at a dose of 400 mg daily and the women in group 2 ( n = 150) received an i.m. dose of 250 mg 17OHP‐C once a week. Transvaginal sonography was repeated every 3 weeks until 36 gestational weeks or the occurrence of preterm labor. Results: A total of 304 singleton pregnant women between 16 and 24 gestational weeks with CL < 25 mm were enrolled in our study. The rates of preterm birth were 10.4% in the progesterone group and 14% in the 17OHP‐C group: a difference that was not statistically significant ( P = 0.416). Moreover, 264 participants underwent ultrasound examination five times and CL changes were studied for 15 weeks. The results showed that the CL changes over 15 weeks were statistically significant ( P < 0.001), but the method of intervention (progesterone/17OHP‐C) had no significant effect on CL change ( P = 0.64). Conclusion: Our findings showed that vaginal progesterone and 17OHP‐C had the same effect on the risk of preterm labor in asymptomatic women with a sonographically short cervix. We detected no significant difference between the effect of 17OHP‐C and vaginal progesterone on CL changes over time.